2006
DOI: 10.1038/sj.jcbfm.9600225
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ischemic Neuronal Death by Intravenous Infusion of a Ginseng Saponin, Ginsenoside Rb1, That Upregulates Bcl-xL Expression

Abstract: Almost all agents that exhibit neuroprotection when administered into the cerebral ventricles are ineffective or much less effective in rescuing damaged neurons when infused into the blood stream. Search for an intravenously infusible drug with a potent neuroprotective action is essential for the treatment of millions of patients suffering from acute brain diseases. Here, we report that postischemic intravenous infusion of a ginseng saponin, ginsenoside Rb(1) (gRb(1)) (C(54)H(92)O(23), molecular weight 1109.46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 37 publications
(44 reference statements)
2
67
0
Order By: Relevance
“…3,4,8) These results suggest that GRb1 might have difficulty entering the CNS. The blood-brain barrier (BBB) or other specialized CNS barriers are the main obstacles to the delivery of many potentially therapeutic and diagnostic compounds to specific areas of the brain.…”
Section: )mentioning
confidence: 82%
See 3 more Smart Citations
“…3,4,8) These results suggest that GRb1 might have difficulty entering the CNS. The blood-brain barrier (BBB) or other specialized CNS barriers are the main obstacles to the delivery of many potentially therapeutic and diagnostic compounds to specific areas of the brain.…”
Section: )mentioning
confidence: 82%
“…6,7) Also, some studies have demonstrated that the effects of 0.1-100 nmol/kg intracerebroventricular GRb1 on ischemic injury are comparable to that of several mg/kg GRb1 systemically administrated. 3,4,8) These results suggest that GRb1 might have difficulty entering the CNS. The blood-brain barrier (BBB) or other specialized CNS barriers are the main obstacles to the delivery of many potentially therapeutic and diagnostic compounds to specific areas of the brain.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…GRb1 (one protopanaxadiol type saponin) is one of the key active compounds of ginseng. Grb1 was recently found to play a role in neuronal cell protection against ischemic insult (15,16). The mechanisms of Grb1 neuroprotection under ischemic stress may be related to the up-regulation of the anti-apoptotic protein expression of Bcl-2 and Bcl-xl and the down-regulation of the proapoptotic protein expression Bax, which inhibited apoptosis by preventing the release of cytochrome c. it is conceivable that Grb1 operates as a roS scavenger, considering its properties in vitro against toxic reactive species, such as hydrogen peroxide and glutamate (13,14).…”
Section: Discussionmentioning
confidence: 99%